DYNAMICS AND PATTERNS OF TRANSNATIONAL STREET BEGGING IN LAGOS AND IBADAN METROPOLIS, NIGERIA (2015)
Street begging is a social problem in Nigeria. Although studies have been extensively conducted on street beggars in Nigeria, sufficient attention has not been devoted to transnational street begging as a distinct phenomenon. The continual influx of transnational street beggars into Nigeria makes the investigation into the dynamics and patterns of transnational street begging imperative. The study examined the socio-demographic profile of transnational street beggars in Lagos and Ibadan, their reasons for migrating to Nigeria, their migratory trajectory and network of relationships. The study was exploratory and cross-sectional in design. The strain and migration network theories were used as conceptual framework. Convenience sampling technique was employed for the selection of transnational street beggars. Three hundred and eighty-two respondents were sampled. A semi-structured questionnaire was administered. In addition, three case studies and 13 in-depth interviews were conducted with purposively chosen transnational street beggars. Seven key-informant interviews were held with personnel of the Nigeria Immigration Service, the Nigeria Custom Service, the Nigeria Police, National Agency for the Prohibition of Trafficking in Persons and Other Related Matters (NAPTIP), Oyo State Ministry of Women Affairs, Community Development and Social Welfare. Quantitative data were analysed using frequency distribution, cross-tabulation and chi-square at p>0.05, while qualitative data were content analysed. Respondents’ age was 28.0±1.2years, 79.6% were Nigeriens, 56.3% were females, 61.8% were married and 64.4% had resided in Nigeria for less than a year. Economic hardship in own country was the major factor responsible for their emigration. Migration was essentially facilitated by social/kinship networks dictated by the presence of relatives (51.6%), friends (29.0%) and acquaintances (19.4%) already in Nigeria. Majority (80.6%) confirmed the involvement of other member(s) of their family in street begging. Most resided with their relatives (43.2%) and friends (35.6%), but some lived in rented rooms (14.9%) in lower class neighbourhoods. About 53.4% came to Nigeria because of perceived better opportunity, however, a difference existed in their reasons according to nationality (χ2=18.95). Migration pathway was characterised by a low involvement of smugglers (χ2=0.91). A difference existed in transnational street beggars’ points of entry into Nigeria according to nationality (χ2=122.02). Transnational street beggars contributed to the nation’s insecurity and other environmental and health problems. The porous Nigerian borders, Economic Community of West African States’ treaty on free movement, commonly shared Hausa language, human trafficking networks and lack of specific order for relevant government agencies inhibited effective control of transnational street beggars. Migration of transnational beggars is an all year round activity with more immigrating into Nigeria in September and August. The Nigerian government should ensure that relevant law enforcement agencies are effective in policing the borders and enforcing migration laws.